Speed-up of SOLPS-ITER code for tokamak edge modeling. (5th October 2018) - Kaveeva, E.; Rozhansky, V.; Senichenkov, I.; Veselova, I.; Voskoboynikov, S.; Sytova, E.; Bonnin, X.; Coster, D.
Abstract: Account of drifts and currents dramatically decreases the accessible time step for the integration of time dependent equations of SOLPS-ITER code for edge modeling. Running the code with sophisticated EIRENE Monte-Carlo model for neutrals and large number of fluid equations for multiple ion species makes the computation time unacceptably long. In the paper the main mechanisms leading to the time step limitations caused by drifts are discussed. Several methods of the suppression of these mechanisms are suggested and the results of numerical scheme tests with the applied corrections are presented. Application of these schemes decreases the time of convergence to steady state solution by more than an order of magnitude.